(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Pedagogical terms in the Karakalpak language are one of the main elements of the educational process. They facilitate communication between teachers and students, help to understand the educational methodology and increase the quality of education. However, in the process of globalization, the issue of correct and accurate translation of Karakalpak pedagogical terms into English is of urgent importance. This article examines the problems and solutions in the process of translating pedagogical terms from Karakalpak into English.